Lung-enriched Organisms and Aberrant Bacterial and Fungal Respiratory Microbiota after Lung Transplant - Charlson, Emily S.; Diamond, Joshua M.; Bittinger, Kyle; Fitzgerald, Ayannah S.; Yadav, Anjana; Haas, Andrew R.; Bushman, Frederic D.; Collman, Ronald G. (American journal of respiratory and critical care medicine, 2012)
Long-term survival after lung transplantation is limited by infectious complications and by bronchiolitis obliterans syndrome (BOS), a form of chronic rejection linked in part to microbial triggers. To define microbial populations in the respiratory tract of transplant patients comprehensively using unbiased high-density sequencing. Lung was sampled by bronchoalveolar lavage (BAL) and upper respiratory tract by oropharyngeal wash (OW). Bacterial 16S rDNA and fungal internal transcribed spacer sequencing was used to profile organisms present. Outlier analysis plots defining taxa enriched in lung relative to OW were used to identify bacteria enriched in lung against a background of oropharyngeal carryover. Lung transplant recipients had higher bacterial burden in BAL than control subjects, frequent appearance of dominant organisms, greater distance between communities in BAL and OW indicating more distinct populations, and decreased respiratory tract microbial richness and diversity. Fungal populations were typically dominated by Candida in both sites or by Aspergillus in BAL but not OW. 16S outlier analysis identified lung-enriched taxa indicating bacteria replicating in the lower respiratory tract. In some cases this confirmed respiratory cultures but in others revealed enrichment by anaerobic organisms or mixed outgrowth of upper respiratory flora and provided quantitative data on relative abundances of bacteria found by culture. Respiratory tract microbial communities in lung transplant recipients differ in structure and composition from healthy subjects. Outlier analysis can identify specific bacteria replicating in lung. These findings provide novel approaches to address the relationship between microbial communities and transplant outcome and aid in assessing lung infections.